Preparation of Fe-Mn-Ce-SA adsorbent and Pb2+ removal from aqueous solutions - Xin ZHAO; Luohong ZHANG; Yu WANG; Mengyuan ZHOU; Xuerong CHENG; Haoran YANG (Xi'an Gongcheng Daxue xuebao, 2021)
In order to obtain high performance adsorbent for removing heavy metal lead ions (Pb2+), a new granular adsorbent (Fe-Mn-Ce-SA gel beads) was prepared by coprecipitation and gel method using sodium alginate as skeleton structure. The morphology characteristics of the adsorbent were observed by scanning electron microscope. The adsorption of Pb2+ by Fe-Mn-Ce-SA gel beads in water was studied, and the effects of pH, ion concentration and temperature on the removal rate of Pb2+ were investigated. At the same time, adsorption kinetics and adsorption isotherm experiments were carried out to explore its adsorption laws. The adsorption results show that Fe-Mn-Ce-SA gel beads have high efficiency adsorption properties to Pb2+, when temperatures rises to 298.15 K, pH=5, the ion concentration is 0.1 mol/L, and the adsorption time is 24 h, the Fe-Mn-Ce-SA gel beads for Pb2+ maximum adsorption reached 182.071 mg/g, the adsorption kinetics of gel ball met the secondary kinetic model, and the thermodynamic behavior was in accordance with Freundlich adsorption isothermal model.